Algiers master plan, land use and forced relocation: Monitoring change with a spatial decision support system - Serrai, Sihem Chourouk; Djiar, Kahina Amal (Land use policy, 2024)
Over the past two decades, Algerian authorities have made significant investments in the housing sector, leading to substantial changes in Algiers' urban landscape. The implementation of forced housing relocation programs, such as the Program for the Resorption of Precarious Housing (RHP), has been pivotal in transforming Algiers into the first African city without slums, recognized by the United Nations in 2016. However, the selection of receiving sites has presented challenges for the authorities, as the actual implementation deviated from the initial plans outlined in the PDAU master plan. This study focuses on examining the site selection process for relocation in Algiers and delineating the disparities between planned and implemented land mobilization. Using an integrated approach, the analysis targets an in-depth study of the PDAU documents. It draws on a comprehensive data collection process, complemented by interviews with all stakeholders which have been engaged in either in the relocation operations in Algiers or in the elaboration of the PDAU. Furthermore, the study is supported with by a large cartographic overlay of the PDAU investigated sites, which allows a better understanding of the subject. Similar studies conducted worldwide have shown that failures in master planning often result from difficulties in execution and compliance, which are common issues in developing countries. In Algiers, the slow process of land mobilization has compelled authorities to adopt unplanned alternative solutions, making land management a blind spot in the planning practice and hindering the implementation of the PDAU as well as limiting the monitoring of urban expansion and development. Additionally, the study shows that despite attempts to incorporate a Spatial Decision Support System (SDSS) within the PDAU, its execution was to a large extent clearly ineffective. The paper contends that failures in urban land management and data collection constitute weak links impeding spatial development. This has shed light on deficiencies in the cadastral system in Algiers, with ambiguities in the legal framework of land management. The study also shows that the strict adherence to master plans can be challenging when dealing with relocation operations due to various factors. Addressing these issues is crucial for the elaboration of more effective relocation programs. By learning from the gaps and weaknesses in the selection process and implementing improved strategies, Algerian authorities can optimize the outcomes of relocation projects and promote more sustainable urban development. •Urban land, data failures hinder spatial development.•Forced relocation in Algiers exposes cadastral gaps, legal ambiguities.•Land management bridges planning gaps, ensuring effective implementation.•Strict master planning faces challenges in relocation due to various factors.•Local engagement, efficient SDSS data promote sustainable urban development.